Designing Brand Identity with a Mascot Media from Tapanuli Selatan Regency as a Tourism Promotion - Roy Hanafi Rambe; Rani Hermita (CV. Publikasi Indonesia, 2024)
The South Tapanuli Tourism Office is an institution engaged in tourism. This library is present to provide services, guidance, management of Tourism, documents, and archives. However, the existence of the South Tapanuli Tourism Office until now has not had a strong attraction for visitors because it does not have a visual identity. Therefore, a visual identity design was made at the South Tapanuli Regional Tourism Office using a 2D mascot as the main media. The mascot created later has a message, impression, and philosophy as a new spirit for the South Tapanuli Tourism Office. With the presence of the mascot of the South Tapanuli Tourism Office, it is hoped that it will be able to make the tourism office better known to the public with its visual identity.